# How to solve the equation x^8 - 64 = 0?

*print*Print*list*Cite

### 2 Answers

We have to solve x^8 - 64 = 0

Now 64 = 2^6

x^8 - 64 = 0

=> x^8 = 64

=> x^8 = 2^6

=> x = 2^(6/8)

=> x = 2^(3/4)

=> x = 8^(1/4)

=> x= sqrt [2*sqrt 2] and x = -sqrt [2*sqrt 2]

**The values of x are x=sqrt [2*sqrt 2] and x=-sqrt [2*sqrt 2]**

Let's recall first the formula for the difference of squares:

a^2 - b^2 =(a-b)(a+b)

Now,we'll put a^2 = x^8 = (x^4)^2 and b^2 = 64 = 8^2

We'll re-write the given equation, emphasizing on the difference of squares:

(x^4)^2 - 8^2 = (x^4 - 8)(x^4 + 8)

x^4 - 8 is also a difference o squares, whose terms are: a = x^2 and b = 2sqrt2

(x^4 - 8)(x^4 + 8) = (x^2 - 2sqrt2)(x^2 + 2sqrt2)(x^4 + 8)

Now, we'll solve the equation:

x^8 - 64 = 0

x^8 - 64 = (x^2 - 2sqrt2)(x^2 + 2sqrt2)(x^4 + 8)

(x^2 - 2sqrt2)(x^2 + 2sqrt2)(x^4 + 8) = 0

x^2 - 2sqrt2 = 0

x^2 = 2sqrt2

x1 = +sqrt(2sqrt2)

x2 = -sqrt(2sqrt2)

x^2 + 2sqrt2 = 0

x3 = +i*sqrt(2sqrt2)

x4 = -i*sqrt(2sqrt2)

**The only real roots of the equation are {+sqrt(2sqrt2) ; -sqrt(2sqrt2)}.**